2011
DOI: 10.3109/13697137.2010.539723
|View full text |Cite
|
Sign up to set email alerts
|

Glucose tolerance of premenopausal women after menopause due to surgical removal of ovaries

Abstract: The impairment of carbohydrate metabolism due to an abrupt decrease in natural estrogen levels should be considered before removing the ovaries during hysterectomy in premenopausal patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…Insulin resistance develops after OVX in rodents (48, 54) and menopause or hysterectomy in humans (12,36) via mechanisms that are incompletely understood but that likely involve increased accretion of WAT. In the current study, OVX caused a reduction in insulin sensitivity in LCR but not HCR rats.…”
Section: Discussionmentioning
confidence: 98%
“…Insulin resistance develops after OVX in rodents (48, 54) and menopause or hysterectomy in humans (12,36) via mechanisms that are incompletely understood but that likely involve increased accretion of WAT. In the current study, OVX caused a reduction in insulin sensitivity in LCR but not HCR rats.…”
Section: Discussionmentioning
confidence: 98%
“…Bilateral oophorectomy (BSO) abruptly decreases the production of estrogens, and is followed by post-glucose challenge hyperinsulinemia, implying insulin resistance (13). In rats, BSO decreased insulin-mediated glucose uptake via an impaired insulinstimulated translocation of GLUT4 to the plasma membrane (11,14) and decreased protein expression of glycogen synthase (14).…”
mentioning
confidence: 99%
“…88,89 The prevalence of glucose intolerance (diabetes mellitus or impaired glucose tolerance) was 26% in women who had natural menopause. 47 Pirimoglu et al 90 reported that 17 of 30 women who had undergone oophorectomy developed glucose intolerance at the end of 12 months. 90 Therefore, surgical menopause may be more severe with regard to the risk for development of glucose intolerance.…”
Section: Discussionmentioning
confidence: 98%
“…47 Pirimoglu et al 90 reported that 17 of 30 women who had undergone oophorectomy developed glucose intolerance at the end of 12 months. 90 Therefore, surgical menopause may be more severe with regard to the risk for development of glucose intolerance. In contrast with natural menopause, women who underwent bilateral oophorectomy had a greater risk of developing CHD.…”
Section: Discussionmentioning
confidence: 98%